Pengaruh Harga, Brand Engagement dan Brand Love Terhadap Keputusan Pembelian pada Pengguna Smartphone Apple (Studi pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Islam Malang) - Malika, Indah Putri; Rachma, N; Rahman, Fahrurrozi (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to examine the effect of price, brand engagement, and brand love variables on the purchasing decisions of apple smartphone users, focusing on students of the faculty of economics and business , Universitas Islam Malang, class of 2021. The research sample was 110 respondents determined based on the malhotra formula, with a purposive sampling technique. Data collection was carried out by distributing questionnaires to respondents who met the criteria. The data analysis methods used include validity test, reliability test, normality test, classical assumption test, multiple linear regressions analysis, F test, t test, and coefficient of determination (R2) test. The findings of this study indicate that the variables price, brand engagement and brand love simultaneously have a positive and significant effect on purchasing decisions, and each independent variable has a significant partial effect on the dependent variable. Keywords: Purchase Decision, Price, Brand Engagement, Brand Love